The Influence Of Work Motivation On Employee Performance Mcdonald'S R. Soekamto Palembang - Desfitrina Desfitrina; Zulfadhli Zulfadhli; Afri Alfarezi Afri Alfarezi (Utan Kayu Publishing, 2024)
This study aims to determine the effect of work motivation on the performance of McDonald's R.Soekamto Palembang employees. The data collection technique used in this study is by giving a set of questions or written statements to respondents using a questionnaire to answer. The questionnaire was given to employees consisting of several about work motivation and employee performance. The data analysis technique used in this research is quantitative analysis. Based on the results of the research that has been done, it is found that there is an effect of work motivation on the performance of McDonald's R.Soekamto Palembang employees. This is indicated by the t-count value of 7.395 with a significant 0.000. The T-Table value obtained from (n-k-1) in the distribution table is 1.173.